“¡Desperta Polska!” by Eduardo Pondal in the Context of the Polish Struggle for Independence - Boguszewicz, Maria (Madrygal. Revista de Estudios Gallegos, 2015)
In the later years of his life, Eduardo Pondal wrote a poem entitled “¡Desperta Polska!”. This poem was dedicated to the struggle for independence in this country which was at the time divided between the three different partitions from the late eighteenth century and later disappeared from the map. The aim of this article is to place the poem in its historical context (Polish and Galician) thanks to which we will obtain further reflection on the vision that Pondal had about Galicia and its role in history.